Question
upstudy study bank question image url

a \( \sqrt{75}+\sqrt{27}-\sqrt{12} \) b \( \frac{11^{n+1} 10^{n-1}}{2^{n-1} 55^{n+1}} \) Solve for \( x \)

Ask by Stanley Delgado. in South Africa
Feb 24,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

a) \( 6\sqrt{3} \) b) \( \frac{1}{25} \)

Solution

It appears you have two separate problems. (There is no variable x in the expressions you provided.) I’ll simplify each one step‐by‐step. ────────────────────────────── Problem (a): Simplify √75 + √27 − √12. Step 1. Write each square root in simplified form by factoring out perfect squares: • √75 = √(25·3) = √25 · √3 = 5√3 • √27 = √(9·3) = √9 · √3 = 3√3 • √12 = √(4·3) = √4 · √3 = 2√3 Step 2. Substitute these into the expression:   √75 + √27 − √12   = 5√3 + 3√3 − 2√3 Step 3. Combine like terms (all terms are multiples of √3):   5√3 + 3√3 − 2√3 = (5 + 3 − 2)√3 = 6√3 Thus, the simplified result for (a) is 6√3. ────────────────────────────── Problem (b): Simplify (11^(n+1) · 10^(n−1)) / (2^(n−1) · 55^(n+1)). Step 1. Express 10 and 55 in terms of their prime factors:   10 = 2 · 5   55 = 5 · 11 Step 2. Rewrite the expression using these factors:   10^(n−1) = (2·5)^(n−1) = 2^(n−1) · 5^(n−1)   55^(n+1) = (5·11)^(n+1) = 5^(n+1) · 11^(n+1) Therefore, the expression becomes:   [11^(n+1) · (2^(n−1) · 5^(n−1))] / [2^(n−1) · (5^(n+1) · 11^(n+1))]. Step 3. Cancel common factors:  • The factor 11^(n+1) in the numerator and denominator cancels.  • The factor 2^(n−1) cancels as well. This leaves:   5^(n−1) / 5^(n+1). Step 4. Simplify using the law of exponents (a^(m)/a^(n) = a^(m−n)):   5^(n−1) / 5^(n+1) = 5^[(n−1) − (n+1)] = 5^(−2) = 1/5^2 = 1/25. Thus, the simplified result for (b) is 1/25. ────────────────────────────── Conclusion: a) √75 + √27 − √12 = 6√3 b) (11^(n+1) · 10^(n−1)) / (2^(n−1) · 55^(n+1)) = 1/25 If you intended "Solve for x" in another context or if there is an equation involving x that was not provided, please clarify so I can help further.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

Let’s break it down step by step! For part \( a \), we simplify the expression \( \sqrt{75} + \sqrt{27} - \sqrt{12} \): - \( \sqrt{75} = \sqrt{25 \times 3} = 5\sqrt{3} \) - \( \sqrt{27} = \sqrt{9 \times 3} = 3\sqrt{3} \) - \( \sqrt{12} = \sqrt{4 \times 3} = 2\sqrt{3} \) Now, combine them: \[ 5\sqrt{3} + 3\sqrt{3} - 2\sqrt{3} = (5 + 3 - 2)\sqrt{3} = 6\sqrt{3} \] For part \( b \), let’s simplify the expression \( \frac{11^{n+1} 10^{n-1}}{2^{n-1} 55^{n+1}} \): - Recognize that \( 55^{n+1} = (5 \times 11)^{n+1} = 5^{n+1} \times 11^{n+1} \) - Thus, we rewrite it as: \[ \frac{11^{n+1} 10^{n-1}}{2^{n-1} \times 5^{n+1} \times 11^{n+1}} = \frac{10^{n-1}}{2^{n-1} \times 5^{n+1}} \] - Now express \( 10^{n-1} = 2^{n-1} \times 5^{n-1} \): \[ \frac{2^{n-1} \times 5^{n-1}}{2^{n-1} \times 5^{n+1}} = \frac{1}{5^2} = \frac{1}{25} \] So, the answers are: - \( a = 6\sqrt{3} \) - \( b = \frac{1}{25} \) Enjoy your math journey!

Related Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy